Phytochemical, Antibacterial, Antifungal, and Hemagglutination Screening of Quercus agrifolia Nee Root Extracts - Wahab, Abdul; Farid, Arshad; Muzammal, Muhammad (UI Scholars Hub, 2022)
In the current study, the roots of Quercus agrifolia Nee were subjected to phytochemical analysis to determine the presence of various compound groups. To explore the effect of Quercus agrifolia Nee roots, we evaluated four solvent extracts, namely, crude ethanolic extract (CEE), n-hexane, chloroform (CHCl3), and ethyl acetate (EtOAc), for their antibacterial, antifungal, and hemagglutination activities. Agar well diffusion and agar tube dilution methods were used to determine the antibacterial and antifungal effects, respectively, and hemagglutination activity was measured against human erythrocyte blood groups. The qualitative phytochemical analysis of the solvent extracts of Quercus agrifolia Nee roots showed the presence of different classes of compounds, i.e., flavonoids, coumarins, terpenoids, etc. The CEE and various fractions were tested against Escherichia coli, Listeria monocytogenes, Alcaligenes faecalis, and Pseudomonas aeruginosa, with CEE exhibiting the widest zone of inhibition against A. faecalis (30 mm) and moderate activities against P. aeruginosa (18 mm%), L. monocytogenes (18 mm%), and E. coli (20 mm%). The n-hexane fraction and the remaining fractions had moderate to good activity against all the four bacterial strains. The antifungal ability of plant roots was also tested against four separate fungal strains, i.e., Alternaria solani, Aspergillus niger, Triticum harzianum, and Fusarium oxysporium, and the n-hexane extract showed a higher activity than the CEE. During the investigation by hemagglutination assay, some solvent extracts exhibited a low amount of lectin complex in the selected plant. The current study revealed that the roots of Quercus agrifolia Nee has an ideal medicinal viability and contains a diverse range of phytochemical classes. This research is the first systematic study of Quercus agrifolia Nee roots, demonstrating its versatility in a variety of biological activities.